Integrasi Akal, Wahyu, Dan Empirisme Dalam Konstruksi Epistemologi Sains Islam Modern - Muhamad Abdul Gofur; Aisyah .; Lulu Raudhatul Bahriyah; Dewi Indrawati (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
The development of modern science rooted in the secular-positivistic paradigm has produced an epistemological dichotomy between religious and secular knowledge, causing reason, revelation, and empiricism to be frequently understood as separate or even contradictory sources of knowledge. This article critically examines the relationship and possible integration of these three epistemic sources as a foundation for constructing modern Islamic science. This study employs a qualitative library research method with a descriptive-analytical approach, examining primary sources including the Qur'an, hadith, and the works of classical and contemporary thinkers, as well as secondary sources consisting of nationally and internationally indexed journal articles published within the last five years (2021-2026). Data were analyzed through content analysis involving reduction, categorization, interpretation, and synthesis. The findings show that Islamic epistemology does not position reason, revelation, and empiricism as opposing entities, but rather as a layered epistemic structure that complements one another within the framework of tawhid, as reflected in the synthesis of bayani, burhani, and irfani reasoning, as well as in the ideas of the Islamization of knowledge (Al-Attas, Al-Faruqi) and the Islamic scholarship paradigm (Kuntowijoyo, Amin Abdullah). This article proposes a non-dichotomous integration model in which revelation functions as an axiological and teleological framework, reason as an analytical-rational instrument, and empiricism as a method for verifying empirical reality, which together form a holistic and ethical epistemology of Islamic science relevant to addressing contemporary civilizational challenges